Dishonest conformity in peer review. (1st September 2015) - Shibayama, Sotaro; Baba, Yasunori
Abstract : Honesty in scientific publication is critical for scientific advancement, but dishonesty is commonly and increasingly observed in misconduct and other questionable practices. Focusing on dishonest conformity in peer review, in which authors unwillingly obey referees' instructions in order to have their papers accepted even if the instructions contradict the authors' scientific belief, the current study aims to investigate the determinants of dishonesty. Drawing on survey data of Japanese life scientists, this study shows that the conflict between authors and referees in peer review is common. A majority of scientists follow referees' instructions rather than refute them. The results suggest that conformity occurs more frequently (1) in biology than in medicine and agriculture, (2) when authors are in strong scientific competition, (3) if authors are associate professors rather than full professors, (4) if authors have no foreign research experience, and (5) in low-impact journals rather than in medium-impact journals.